Fiscal distress in Karnataka: some issues - Gayithri, K. (2003)
Fiscal stress in Karnataka has been on the increase in the late nineties. This is the outcome of a fall in the revenue resources of the State government coupled with unbridled revenue expenditure. As a result, the State, which had achieved revenue surplus in the mid-nineties, has relapsed into revenue deficit. The paper delineates the fiscal situation in Karnataka and factors responsible for the growing fiscal stress by using an inter-state analysis of fiscal indicators as well as the State's own indicators over time. The paper addresses, in particular, the growing fiscal costs as well as issues associated with industrial incentive schemes in the State during the reform phase. - Reproduced.
Keywords: Economic recession - India - Karnataka; Economic recession